THE MARKETING STRATEGY OF MADURA TOURISM INDUSTRY AREA TROUGH SUSTAINABLE DEVELOPMENT BASED GENDER - Mohammad Taqiuddin Mohammad; Abdul Hannan; Alan Suud Maadi (Jurnal Ekonomi dan Bisnis Islam | Journal of Islamic Economics and Business, 2019)
Being declared in 2015 in Rio De Janeiro, Brazil, sustainable development goals (SDGs) has an aim to answer various humanitarian-environment crisis of millennium era (MDGs). One of the main problems which become a focus is woman’s participation. Especially in development context, whether in international, national, or local scope. This paper entitle, The Marketing Strategy of Madura Tourism Industry Area trough Sustainable Development Based Gender. In particular, this study has an aim to analyze the existential of Madura woman, dealing with the area development based SDGs. Various crucial issues which become a focus of this study namely; the dynamic Madura tourism industry, sustainable development concept, and development idea based gender. The three crucial issues above will be elaborated based on the three research problems below: 1).How is the existence of Madura tourism? 2).Whatis the definition of sustainable development? 3). How is the position of gender plays a role and strategic function in marketing activity of Madura tourism industry for the next? This study is qualitative method. The data of this paper is from two sources namely primary and secondary data. The theory perspective of this study is using area marketing theory of Richard Florida and Femenis George Ritzer theory. In general, this paper has an aim to describe how the dynamic Madura tourism industry is, this study has big contribution in offering the Madura development idea, especially in promoting the local industry area to sustainable development area carrying the spirit of equality.  Keywords: Marketing area, Madura tourism, sustainable development, Gender.